2021
DOI: 10.3390/ijms23010377
|View full text |Cite
|
Sign up to set email alerts
|

Animal Model for Glucocorticoid Induced Osteoporosis: A Systematic Review from 2011 to 2021

Abstract: Clinical and experimental data have shown that prolonged exposure to GCs leads to bone loss and increases fracture risk. Special attention has been given to existing emerging drugs that can prevent and treat glucocorticoid-induced osteoporosis GIOP. However, there is no consensus about the most relevant animal model treatments on GIOP. In this systematic review, we aimed to examine animal models of GIOP centering on study design, drug dose, timing and size of the experimental groups, allocation concealment, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 103 publications
(89 reference statements)
0
9
0
Order By: Relevance
“…To detect whether QCT has effects on anti-osteoporosis, dexamethasone (DEX), a kind of glucocorticoid, was used to construct a zebrafish model [ 32 ]. We used alizarin red staining to investigate the effects of bone formation ( Figure 7 A).…”
Section: Resultsmentioning
confidence: 99%
“…To detect whether QCT has effects on anti-osteoporosis, dexamethasone (DEX), a kind of glucocorticoid, was used to construct a zebrafish model [ 32 ]. We used alizarin red staining to investigate the effects of bone formation ( Figure 7 A).…”
Section: Resultsmentioning
confidence: 99%
“…(2,3) GIO is the leading cause of secondary osteoporosis (a condition caused by another disease or treatment of another disease) and has been well documented in both the basic science and clinical literature. (4)(5)(6) GIO significantly increases the risk of osteoporosis-related fractures in chronic GC users and leads to increased morbidity and mortality. (7)(8)(9) Current therapeutic options to treat GIO include bisphosphonates, denosumab, and intermittent parathyroid hormone (iPTH), among others.…”
Section: Introductionmentioning
confidence: 99%
“…Through a preliminary search of eight databases, 445 studies were identified. In addition, seven articles from our records met the requirements for this meta-analysis but did not appear in the search results, and we included those ( Xavier et al, 2021 ). After removing duplicate studies, 285 articles remained, and we performed title and abstract readings to exclude 265 articles, including 238 irrelevant studies, 16 studies whose interventions did not meet inclusion requirements, five literature reviews, three conference abstracts, and three articles for which the full text was not available.…”
Section: Resultsmentioning
confidence: 99%